VARIASI GENETIK BEBERAPA POPULASI MERBAU (Intsia bijuga O. Ktze) BERDASARKAN PENANDA ISOENZIM - Tri Pamungkas Yudohartono (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
The objectives of this study were to investigate the level of genetic variation and to describe its distribution within and among populations of merbau. Leaves of wildling were collected from four populations distributed in Papua and Moluccas islands. Genetic variation was detected by isoenzyme markers using four enzyme system i.e. Peraxidae (POD), Esterase (EST), Diaphorase (DIA) and Glutamate Oxaloacetate Transaminase (GOT). The result showed that 17 alleles were identified and distributed on 6 polymorphic loci. The mean percentage of polymorphic loci was 95.8 %. The average genetic diversity within population was 0.049. The UPGMA cluster analysis based on Nei’s standard genetic distance reflected three clusters, i.e. Haltim and Waigo formed first cluster, Nabire formed second cluster, and Seram formed third cluster separated from two other clusters.